Dietary intake and severe early childhood caries in low-income, young children - Evans, E. Whitney (2013)
Evidence suggests that risk for early childhood caries (ECC), the most common chronic infectious disease in childhood, is increased by specific eating behaviors. To identify if consumption of added sugars, sugar-sweetened beverages (SSB), and 100% fruit juice, as well as eating frequency, are associated with severe-ECC (S-ECC), cross-sectional data collected from a sample of low-income, racially diverse children, ages two to six years old, were used. Four-hundred and fifty-four children with S-ECC and 429 caries-free children were recruited in 2004-2008 from three pediatric dental clinics in Columbus, OH, Cincinnati, OH and Washington, D.C. Dietary data were obtained from one parent-completed 24-hour recall and an interviewer-administered food frequency questionnaire (FFQ). Multivariate logistic regression analyses were conducted to assess associations between S-ECC and dietary variables. On average, children with S-ECC consumed 3.2-4.8 fluid ounces more SSB (24HR: 1.80 versus 1.17; p < .001; FFQ: 0.82 versus 0.39; p<.001) and reported significantly more daily eating occasions (5.26 versus 4.72; p<.0001) than caries-free children. After controlling for age, sex, race/ethnicity, maternal education, recruitment site and family size, children with the highest SSB intake were 2.0 to 4.6 times more likely to have S-ECC as compared with those with the lowest intake, depending on dietary assessment method (24HR: OR 2.02; 95% CI: 1.33, 3.06; FFQ: OR 4.63; 95% CI: 2.86, 7.49). The relationship between eating frequency and S-ECC status was no longer significant in multivariate analyses. Specific dietary guidance for parents of young children, particularly regarding SSB consumption, could help reduce S-ECC prevalence.